Los estudios de opinión pública - Ruiz Restrepo, Jaime (La Sociología en sus Escenarios, 2009)
Abstract A popular representation of the social researcher is a figure wearing a paper holder and who comes to you on the street and ask if you have time to answer a few questions. If you agree to be questioned, it is very likely that the questions are on their political views, their intentions to vote, or about their preferences with respect to powdered soap for washing clothes, or options on vacationing abroad or on television programs, or on any of a multitude of other possibilities. All these things come under the general heading of "public opinion surveys, and can take many forms. Resumen Una representación popular del investigador social es el de una figura que lleva un porta-papeles y que se acerca a usted en la calle, y le pregunta si tiene tiempo para responder a unas pocas preguntas. Si usted está de acuerdo en ser interrogado, es muy probable de que las preguntas sean sobre sus opiniones políticas, sus intenciones de votar, o sobre sus preferencias con respecto al jabón en polvo para lavar ropa, o sobre opciones de vacacionar en el extranjero, o sobre programas de televisión, o sobre cualquiera de una multitud de otras posibilidades. Todas esas cosas vienen bajo el encabezamiento general de "estudios de opinión pública", y pueden tomar muchas formas.